Evaluation of the impact of fetal fibronectin test implementation on hospital admissions for preterm labour in Ontario: a multiple baseline time‐series design. (2nd December 2013) - Fell, DB; Sprague, AE; Grimshaw, JM; Yasseen, AS; Coyle, D; Dunn, SI; Perkins, SL; Peterson, WE; Johnson, M; Bunting, PS; Walker, MC
<x xml:space="preserve">Abstract</x> Objective To determine the impact of a health system‐wide fetal fibronectin (fFN) testing programme on the rates of hospital admission for preterm labour (PTL). Design Multiple baseline time‐series design. Setting Canadian province of Ontario. Population A retrospective population‐based cohort of antepartum and delivered obstetrical admissions in all Ontario hospitals between 1 April 2002 and 31 March 2010. Methods International Classification of Diseases codes in a health system‐wide hospital administrative database were used to identify the study population and define the outcome measure. An aggregate time series of monthly rates of hospital admissions for PTL was analysed using segmented regression models after aligning the fFN test implementation date for each institution. Main outcome measure Rate of obstetrical hospital admission for PTL. Results Estimated rates of hospital admission for PTL following fFN implementation were lower than predicted had pre‐implementation trends prevailed. The reduction in the rate was modest, but statistically significant, when estimated at 12 months following fFN implementation (−0.96 hospital admissions for PTL per 100 preterm births; 95% confidence interval [CI], −1.02 to −0.90, P = 0.04). The statistically significant reduction was sustained at 24 and 36 months following implementation. Conclusions Using a robust quasi‐experimental study design to overcome confounding as a result of underlying secular trends or concurrent interventions, we found evidence of a small but statistically significant reduction in the health system‐level rate of hospital admissions for PTL following implementation of fFN testing in a large Canadian province.